Formation Mechanism and Stability Analysis of the Hejia Landslide - Hao Zhang; Zaiqiang Hu; Xingzhou Chen; Hongru Li (Advances in Materials Science and Engineering)
The existing research data show that, after reservoir impoundment, due to the repeated rise and fall of water level and water-rock interaction, the mechanical parameters of landslide are reduced, which will have an adverse effect on the stability of landslide. Therefore, sufficient attention must be paid to the stability of slope after reservoir impoundment. Hejia landslide is the largest landslide near the bank of Miaojiaba hydropower station, and its stability plays an important role in the normal operation of the hydropower station. Through field investigation and analysis of regional geological conditions, it is concluded that Hejia landslide is a large-scale landslide, through long-term sliding-bending deformation; it is generated from the external hard rock with thick layers and sliding zone for layered soft rock; the formation mechanism of landslide is as follows: (1) high-steep and hard-soft layered slope is the slope structure condition that caused the large landslide; (2) the existence of thick soft rock belt provides material conditions for the formation of slip surface; (3) certain air conditions provide displacement space for the separation and disintegration of the sliding body, and the landslide is stable at present. Numerical analysis results show that reservoir impoundment will adversely affect the stability of landslide. In order to ensure the normal operation of power station, certain engineering measures must be taken to treat Hejia landslide. After taking measures, years of monitoring data show that the deformation of Hejia landslide tends to be stable, and the current operation is normal, indicating that the engineering treatment measures are reasonable and feasible.